JINGLE – IV. Dust, H i gas, and metal scaling laws in the local Universe. Issue 3 (2nd June 2020) - De Looze, I; Lamperti, I; Saintonge, A; Relaño, M; Smith, M W L; Clark, C J R; Wilson, C D; Decleir, M; Jones, A P; Kennicutt, R C; Accurso, G; Brinks, E; et al.
ABSTRACT: Scaling laws of dust, H i gas, and metal mass with stellar mass, specific star formation rate, and metallicity are crucial to our understanding of the build-up of galaxies through their enrichment with metals and dust. In this work, we analyse how the dust and metal content varies with specific gas mass ( M H i / M ⋆ ) across a diverse sample of 423 nearby galaxies. The observed trends are interpreted with a set of Dust and Element evolUtion modelS (DEUS) – including stellar dust production, grain growth, and dust destruction – within a Bayesian framework to enable a rigorous search of the multidimensional parameter space. We find that these scaling laws for galaxies with −1.0 ≲ log M H i / M ⋆ ≲ 0 can be reproduced using closed-box models with high fractions (37–89 per cent ) of supernova dust surviving a reverse shock, relatively low grain growth efficiencies (ϵ = 30–40), and long dust lifetimes (1–2 Gyr). The models have present-day dust masses with similar contributions from stellar sources (50–80 per cent ) and grain growth (20–50 per cent ). Over the entire lifetime of these galaxies, the contribution from stardust (>90 per cent ) outweighs the fraction of dust grown in the interstellar medium (<10 per cent ). Our results provide an alternative for the chemical evolution models that require extremely low supernova dust production efficiencies and short grain growth time-scales to reproduce local scaling laws, and could help solving the conundrum on whether or not grains can grow efficiently in the interstellar medium.